Assessment of the antidiarrhoeal properties of the aqueous extract and its soluble fractions of Chebulae Fructus (Terminalia chebula fruits). (1st September 2016) - Sheng, Zunlai; Yan, Xin; Zhang, Ruili; Ni, Huilin; Cui, Yuanxu; Ge, Junwei; Shan, Anshan
Abstract: Context Chebulae Fructus is used as an herbal remedy for diarrhoea in traditional Chinese medicine. However, there is no scientific evidence to support its antidiarrhoeal activity. Objective This study evaluates the antidiarrhoeal properties of Chebulae Fructus aqueous extract (CFAE) and determines the active fraction. Materials and methods The antidiarrhoeal effect of CFAE (200–800 mg/kg) was investigated by determining the wet dropping, intestinal transit in BALB/c mice and enteropooling in Wister rats. The protective effects of the CFAE on the intestinal and liver were tested by histopathological analyses. The antidiarrhoeal fraction was determined by castor oil-induced diarrhoea and its main constituents were identified by HPLC-ESI-MS. Results The extract at doses of 200, 400 and 800 mg/kg reduced the diarrhoea by 9.1, 40.0 and 58.2% and inhibited intestinal transit by 18.3, 24.1 and 35.7%, respectively. Additionally, the CFAE (200, 400 and 800 mg/kg) decreased the volume of enteropooling by 47.1, 58.8 and 64.7%, respectively. Mice treated with castor oil presented morphological alterations in the small intestine and the liver. However, the lesions of mice treated with CFAE were alleviated. Moreover, the ethyl acetate fraction was the active fraction of CFAE, the fraction (41.7, 83.4 and 166.8 mg/kg) reduced the diarrhoea by 9.1, 38.2 and 54.5%, respectively. The major components of the ethyl acetate fraction were tannins, including gallic acid, 3, 4, 6-tri- O -galloyl-β-d -Glc, corilagin and ellagic acid according to the HPLC-ESI-MS analysis. Conclusion The CFAE possessed antidiarrhoeal property and the ethyl acetate fraction was its main active fraction.